NMR SPECTRA OF PHOSPHORYLATED CARBAMIDE-CONTAINING HETEROCYCLES: PECULIARITIES OF CHEMICAL SHIFTS FROM THE VALENCE STATE OF THE PHOSPHORUS AND THE SIZE OF THE CYCLE - Bakibayev A.A.,; Zhumanov K.B.,; Panshina S.,; Malkov V.S.,; Gorbin S.,; Khrebtova D.V.,; Ponomarenko O.V.,; Tsoy I.G.,; Matniyazova G. K.,; Baybazarova Е.А., (Academic Scientific Journal of Chemistry, 2019)
The article discusses the results of using NMR spectroscopy to study the structure and flexibility of the skeleton of the analyzed molecules of phosphaze compounds and the electronic environment of nitrogen and phosphorus atoms. The authors carried out a cumulative system analysis of chemical shifts in the 31P and 13C NMR spectra of 89 phosphorus derivatives of carbamidecontaining heterocycles, which differ in the valence state of the phosphorus atom, the size of the cycle and the method of cycle junction.